Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1289/ehp.00108s2307
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of Clewell et al. PBPK model of trichloroethylene kinetics.

Abstract: A physiologically based pharmacokinetic model for trichloroethylene (TCE) in rodents and humans was calibrated with published toxicokinetic data sets. A Bayesian statistical framework was used to combine previous information about the model parameters with the data likelihood, to yield posterior parameter distributions. The use of the hierarchical statistical model yielded estimates of both variability between experimental groups and uncertainty in TCE toxicokinetics. After adjustment of the model by Markov ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Monte Carlo methods are based on a Bayesian statistical approach that involves the use of experimental data to update estimates of a hypothesized "prior" probability distribution for one or more model parameters. Examples of Monte Carlo methods applied to PBPK models can be found in [22][23][24][25][26][27][28][29][30][31].…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
“…Monte Carlo methods are based on a Bayesian statistical approach that involves the use of experimental data to update estimates of a hypothesized "prior" probability distribution for one or more model parameters. Examples of Monte Carlo methods applied to PBPK models can be found in [22][23][24][25][26][27][28][29][30][31].…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
“…The same arguments as for animal experiments can be made in favour or the use of population models in that context. For further discussion, the reader is referred to our recent population TK analyses of volunteer exposures to tetrachloroethylene (Bois et al, 1996a; , benzene (Bois et al, 1996b) , trichloroethylene (Bois, 2000b;Bois, 2000a) , or 1,3-butadiene . The inclusion of genotype information in such analyses is straightforward (Johanson et al, 1999) , and should see considerable development in the near future.…”
Section: Human Volunteers Studiesmentioning
confidence: 99%
“…Administered doses (lifetime average daily doses in mg/kg/day intake) and internal doses based on the pharmacokinetic modeling of Fisher (9), Clewell et al (6), and Bois (29,30) are also shown. These bioassays have been reviewed and their suitability for risk assessment commented on in more detail by Bull (16) and the U.S. EPA (1,2).…”
Section: Pharmacokinetic Models and Internal Dosesmentioning
confidence: 99%
“…Clewell et al (6) and Bois (29) in his reanalysis of the Clewell pharmacokinetic model have produced estimates of the reactive thiol production in rat and human kidneys at relevant dose levels (Table 10), and these are used in the following quantitative analysis. The Clewell and Bois-C estimates are quite different, almost exactly 100-fold different.…”
Section: Rat Kidney Tumorsmentioning
confidence: 99%